Effects of a Four-Week Climbing Intervention on Motor Abilities in PE Class - BALLA, Béla József; FINTA, István; BOROS-BALINT, Iuliana (Studia Universitatis Babeș-Bolyai. Educatio artis gymnasticae, 2025)
Introduction: Regular climbing can contribute to the maintenance and development of both mental and physical well-being. Studies investigate how regular indoor climbing affects the strength endurance of specific trunk and arm muscles, as well as the joint mobility of the trunk and hips in different planes. Objective: The aim of this study was to evaluate the influence of climbing on adolescents' static strength, muscular endurance, lower limb explosive strength, and flexibility within a 4-week program integrated into the school physical education curriculum. Material and methods: A total of 48 adolescents were randomly assigned to an intervention group (IG; n = 21; 8 boys, 13 girls; M = 15.33 ± 0.50 years) and a control group (CG; n = 27; 9 boys, 18 girls; M = 15.54 ± 0.50 years), with similar gender distributions across both groups. Results: After the four-week intervention, there was a significant change in the hand grip strength of the IG, namely, the strength of both the dominant (from M = 30.11, SD = 8.13 kg to M = 26.84, SD = 7.89 kg), and the non-dominant hand significantly decreased (from M = 26.84, SD = 7.98 kg to M = 24.00, SD = 7.91 kg). This phenomenon can also be observed in the CG. Conclusion: Considering the available facilities, the age group, and the allocated time for the intervention (4 weeks, 2 sessions per week, 50 minutes each), these conditions appear insufficient to elicit a significant positive change in the examined abilities. Article history: Received 2025 October 17; Revised 2025 November 14; Accepted 2025 November 17 Available online 2025 November 20; Available print 2025 November 30